The sweet and sour sides of trypanosome social motility. Issue 4 (April 2023) - Shaw, Sebastian; Roditi, Isabel
Highlights: Social motility (SoMo) is the ability of Trypanosoma brucei procyclic forms to generate and respond to pH gradients. The differential responses of early and late procyclic forms to pH results in the self-organisation of communities on semi-solid surfaces. pH gradients occur in the tsetse fly host and might be used by the parasite to guide migration. pH sensing requires specific adenylate cyclases and a cAMP response protein, CARP3. T. brucei encodes a large number of adenylate cyclases that are likely to sense other environmental signals, enabling parasites to home into specific tissues in both hosts. Abstract: Recent studies showed that the formation of elegant geometric patterns by communities of Trypanosoma brucei on semi-solid surfaces, dubbed social motility (SoMo) by its discoverers, is a manifestation of pH taxis. This is caused by procyclic forms generating and responding to pH gradients through glucose metabolism and cAMP signalling. These findings established that trypanosomes can sense and manipulate gradients, potentially helping them to navigate through host tissues. At the same time, the host itself and bystanders such as endosymbionts have the potential to shape the environment and influence the chances of successful transmission. We postulate that the ability to sense and contribute to the gradient landscape may also underlie the tissue tropism and migration of other parasites in their hosts.